Mental Health Profile of Class IX Students at Airpura 2 Middle School - Wulansari, Vikka (Holistic Science, 2022)
Mental health is an important component in every level of human life, from childhood, adolescence to adulthood. In fact, it is often mentioned that mental conditions in childhood can affect a person's mental development into adulthood. Therefore, it is important for someone to have a healthy mentality from a young age. Metal health is a condition where a person is free from feelings of guilt towards himself, can accept shortcomings or weaknesses, is able to solve problems, has satisfaction in his social life, is happy and has a realistic estimate of himself. A person's mental health means that he is physically healthy and vice versa. The role of parents is very important in maintaining the physical health of children, because the family interacts the longest with children. Nevertheless, there are still many parents who pay attention to their children's physical and never force their will so that mental health is realized. The psychological aspect is a mental health support for students. after the researcher observed that there were still students who did not respect their friends so that there were fights that resulted in the victims of the ridicule.